1986
DOI: 10.1300/j251v05n03_04
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Family Therapy on Addict Family Functioning:

Abstract: Family therapy may help addicts remain drug abstinent by improving family functioning. In a outpatient pilot study eight addict families were evaluated before and after 16 weeks of multiple family therapy (MFT), while the addict was maintained on naltrexone, an opiate antagonist. The Beavers Timberlawn Family Assessment was used to rate videotapes on problem solving, family structure, individual autonomy, and affect. The 8 families showed significant improvement in global functioning, problem solving, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Initially designed as open-ended groups for hospitalized psychotic patients and their families, multiple family groups have over the last 3 decades been used as adjunctive treatments for a wide variety of clinical conditions, including affective disorders (Anderson, Griffin, Rossi, et al, 1986a), schizophrenia (Anderson, Reiss, & Hogarty, 1986b; Falloon, Boyd, McGill, et al., 1985; McFarlane, 1983), eating disorders (Slagerman & Yager, 1989), and substance abuse (Kosten, Hogan, Jalali, et al, 1986). In each of these arenas, clinicians have reported that MFGs seem to increase engagement of patients and families in treatment protocols, improve patients’ social functioning, and at times have a direct impact on patients’ symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Initially designed as open-ended groups for hospitalized psychotic patients and their families, multiple family groups have over the last 3 decades been used as adjunctive treatments for a wide variety of clinical conditions, including affective disorders (Anderson, Griffin, Rossi, et al, 1986a), schizophrenia (Anderson, Reiss, & Hogarty, 1986b; Falloon, Boyd, McGill, et al., 1985; McFarlane, 1983), eating disorders (Slagerman & Yager, 1989), and substance abuse (Kosten, Hogan, Jalali, et al, 1986). In each of these arenas, clinicians have reported that MFGs seem to increase engagement of patients and families in treatment protocols, improve patients’ social functioning, and at times have a direct impact on patients’ symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Although during the nineteen-seventies, the literature and research on multi-family groups are limited, this format became increasingly popular in the treatment of alcohol abuse and the abuse of other drugs (Bergen, 1973;Kaufman & Kaufman, 1979). In the nineteen-eighties, we find references to its application in heroin addiction treatment programs in the therapeutic community (Anton, Hogan, Jalali, Riordan, & Kleber, 1981;Clerici et al, 1988) and for alcoholism and substance abuse (Kosten, Hogan, Jalali, Steidl, & Kleber, 1986;Lovern & Zohn, 1982). From the mid-nineteen-eighties to the mid-nineteen-nineties, we found only a few publications on multifamily group therapy.…”
mentioning
confidence: 99%
“…Central to the effective facilitation of the groups are principles of restoring self-efficacy, vicarious learning, improved communication skills and support (see Kaufman & Kaufman, 1979;McFarlane, 1982;Asen, 2002). Most publications on MFGs appeared between the 1970s (Alger, 1975;Bergen, 1973;Bowen, 1975;Hendricks, 1971;Kaufman & Kaufman, 1977;Laqueur, 1976;Laqueur et al, 1964;McKamy, 1976) and the mid-eighties (Anton et al, 1981;Clerici et al, 1988;Lovern & Zohn, 1982;Nichols, 1985;Kosten et al, 1986;Zimberg, 1982, McFarlane, 1982. McFarlane (1982), for example, developed a multi-family therapy program in a psychiatric hospital because he was convinced that families might learn from each other by seeing parts of themselves in others.…”
Section: Multiple Family Group Interventionsmentioning
confidence: 99%